Lifecycle greenhouse gas emissions and energy cost analysis of flying cars with three different propulsion systems. (10th January 2022) - Liu, Ming; Qian, Yuping; Luo, Yiwei; Hao, Han; Liu, Zongwei; Zhao, Fuquan; Sun, Xin; Xun, Dengye; Geng, Jingxuan
Abstract: Flying cars are expected to play an important role in future transportation, considering their ability to transform transport ecology and improve transportation efficiency. However, the optimal choice of propulsion systems for flying cars is still unclear due to the lack of studies on the environmental and economic impacts of flying cars considering different propulsion systems. Based on the analysis of flying processes and design requirements, we established functional models for flying cars with different propulsion systems and calculated their lifecycle greenhouse gas emissions and average energy costs to investigate the technology pathways. The results demonstrated that the optimal choice of propulsion systems for flying cars critically depends on the designed range. For short-range trips within 190 km, battery electric flying cars show advantages in both emissions and energy cost. For trips with a range of 200–250 km, fuel cell flying cars are the best choice. Internal combustion engine flying cars are currently the only viable option for long-distance transportation higher than 250 km. In particular, the on-going advancements in battery specific energy will further provide battery electric flying cars with environmental and economic competitiveness within larger flying ranges. Flying cars are also competitive in energy costs compared with on-ground vehicles under a wide range of utilization scenarios, demonstrating the possibility of commercialization. Highlights: Battery electric Vertical Takeoff and Landing aircrafts (VTOLs) are highly competitive for short-distance transportation. Fuel cell VTOLs are advantageous for 200–250 km trips. Internal combustion engine VTOLs are suitable for long-distance transportation. VTOLs can help address traffic congestion at a reasonable energy cost.